2008
DOI: 10.1186/1476-511x-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic comparison of triglyceride-rich remnant lipoprotein measurement between a new homogenous assay (RemL-C) and a conventional immunoseparation method (RLP-C)

Abstract: BackgroundIncreased serum remnant lipoproteins are supposed to predict cardiovascular disease in addition to increased LDL. A new homogenous assay for remnant lipoprotein-cholesterol (RemL-C) has been developed as an alternative to remnant-like particle-cholesterol (RLP-C), an immunoseparation assay, widely used for the measurement of remnant lipoprotein cholesterol.MethodsWe evaluated the correlations and data validation between the 2 assays in 83 subjects (49 men and 34 women) without diabetes, hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Although adiponectin is reported to suppress macrophage foam cell transformation in vitro, abnormal remnant lipoproteinemia may strongly affect coronary plaque instability in the patients with stable angina. Omentin-1 is another candidate of anti-RLP-C), because the special surfactant (polyethylenepolyoxybutylene block copolymer) and phospholipase D enhance the affinity to the IDL and chylomicron remnant, respectively 22) . This results in the higher levels of RemL-C, than RLP-C, in the cases with increased IDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adiponectin is reported to suppress macrophage foam cell transformation in vitro, abnormal remnant lipoproteinemia may strongly affect coronary plaque instability in the patients with stable angina. Omentin-1 is another candidate of anti-RLP-C), because the special surfactant (polyethylenepolyoxybutylene block copolymer) and phospholipase D enhance the affinity to the IDL and chylomicron remnant, respectively 22) . This results in the higher levels of RemL-C, than RLP-C, in the cases with increased IDL.…”
Section: Discussionmentioning
confidence: 99%
“…This method utilized surfactant and phospholipase D to selectively solubilize and degrade remnant lipoprotein, while the RLP-C assay was an immune separation assay using an immunoaffinity gel containing antiapoA-1 and anti-apoB-100 monoclonal antibodies 22,23) . This RemL-C assay is adaptable for a universal clinical autoanalyzer, supplying quick and high-throughput measurements.…”
Section: Reml-c a Tg-independent Determinant For %Lipidmentioning
confidence: 99%
“…In the present study, we newly showed increased RemL-C levels on a homogenous asssay in association with lower eGFR values and higher U-ACR values. Although apoB48 is a specific marker of chylomicron and its remnant, other parameters, including RemL-C, are not specific to the chylomicron remnant or VLDL remnant [32][33][34] . Therefore, we interprete our data to indicate that a lower renal funtion and higher level of albuminuria are associated with an increased concentration of either chylomicron remnant, VLDL remnant or both.…”
Section: Discussionmentioning
confidence: 99%
“…The remnant lipoprotein cholesterol (RemL-C) level was measured using a homogenous assay (MetaboRead TM , Kyowa Medex). In our previous studies, the serum concentration of RLP-C was measured using the immunoaffinity separation method 16) ; however, the RLP-C concentration measured using this method is sometimes less than the lower limit of detection in young Japanese women 14) . In the present study, the serum concentration of RemL-C was therefore measured using a newly developed homogenous assay 16) , and no samples were found to contain a concentration below the detection limit.…”
Section: Fructose Glucose Insulin Ffa and Lactatementioning
confidence: 99%